2023
DOI: 10.1097/iop.0000000000002337
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Extraocular Muscle Cross-sectional Area and Correlation With Extraocular Motility and Diplopia Following Teprotumumab for Thyroid Eye Disease

Abstract: To quantify changes in extraocular muscle (EOM) cross-sectional areas (CSA) on orbital imaging in patients with thyroid eye disease before and after teprotumumab treatment, and assess for correlation with clinical outcomes.Methods: This retrospective study included thyroid eye disease patients treated with teprotumumab who had pre-and post-treatment CT imaging. Reformatted oblique coronal images were created for each orbit in a plane perpendicular to the optic nerve. EOM CSA measurements were performed by 2 ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Ugradar et al 15 added that the greatest improvement is in sursumversion. Reshef et al 26 further described clinico-radiological correlations, reporting a reduction in composite motility restriction and total extraocular muscle cross-sectional area. Little information on strabismus was offered in either of the latter 2 studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ugradar et al 15 added that the greatest improvement is in sursumversion. Reshef et al 26 further described clinico-radiological correlations, reporting a reduction in composite motility restriction and total extraocular muscle cross-sectional area. Little information on strabismus was offered in either of the latter 2 studies.…”
Section: Discussionmentioning
confidence: 99%
“…The dissociation between improvements in motility without similarly consistent improvements in strabismus is curious, yet consistent with previous reports. 14,15,26 It is not completely clear how these results can be reconciled. It is possible that the improvements in motility may occur without altering the relative size and strength imbalance between agonists and antagonist EOMs so that strabismus persists.…”
Section: Discussionmentioning
confidence: 99%
“…The authors have read with interest the recent study by Reshef et al, 1 which demonstrated a radiological reduction in extraocular muscle (EOM) cross-sectional area and EOM to orbit ratio following teprotumumab treatment. In this study, the authors aimed to correlate the mechanism of teprotumumab with anatomic changes and clinical response to treatment.…”
Section: To the Editormentioning
confidence: 99%
“…Several research has examined the connection between EOM size and clinical signs of EOM motility, and several of them have found a specific link between radiographic EOM enlargement and motility restriction. The two-dimensional measurement of mean cross-sectional area would give a more precise indication of the true "size" of the muscles, particularly in thyroid eye illness [12][13][14] . A systematic study of human horizontal rectus EOM contractility has demonstrated that EOM morphologic changes in single-plane maximum cross-sectional areas and posterior partial volumes (PPVs) provide accurate and quantitative measures of EOM contractility [15] , which indicated the morphologic changes of EOM in response to EOM strength.…”
Section: Introductionmentioning
confidence: 99%